1997
DOI: 10.1172/jci119683
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the guanylyl cyclase-C gene leads to a paradoxical phenotype of viable but heat-stable enterotoxin-resistant mice.

Abstract: Heat-stable enterotoxins (STa), which cause an acute secretory diarrhea, have been suggested to mediate their actions through the guanylyl cyclase-C (GC-C) receptor. The GC-C gene was disrupted by insertion of neo into exon 1 and subsequent homologous recombination. GC-C null mice contained no detectable GC-C protein. Intestine mucosal guanylyl cyclase activity was ‫ف‬ 16-fold higher in wild-type mice than in the GC-C null mice, and STa-stimulable guanylyl cyclase activity was absent in the null animals. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
113
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(118 citation statements)
references
References 33 publications
3
113
1
1
Order By: Relevance
“…It has recently been shown that ST exposure activates calcium influx through cyclic nucleotide-gated channels in rat colonocytes 6 and in T84 cells, where it is associated with decreased proliferation. 2 However, mice lacking GC-C, Gucy2c 2/2 , are viable and fertile with no apparent defects in intestinal morphology or growth 7,8 and there are no differences in crypt depth or villus height (data not shown). Functional studies established that while colonic ion transport is similar to that observed in wild-type mice, 9 bicarbonate secretion in the duodenum of GC-C null mice is greatly attenuated in response to acid, a major physiologic stimulus of secretion.…”
mentioning
confidence: 96%
“…It has recently been shown that ST exposure activates calcium influx through cyclic nucleotide-gated channels in rat colonocytes 6 and in T84 cells, where it is associated with decreased proliferation. 2 However, mice lacking GC-C, Gucy2c 2/2 , are viable and fertile with no apparent defects in intestinal morphology or growth 7,8 and there are no differences in crypt depth or villus height (data not shown). Functional studies established that while colonic ion transport is similar to that observed in wild-type mice, 9 bicarbonate secretion in the duodenum of GC-C null mice is greatly attenuated in response to acid, a major physiologic stimulus of secretion.…”
mentioning
confidence: 96%
“…Gene deletion of murine GC-A, GC-C, ANP, BNP, and CNP along with transgenic over-expression of ANP and BNP have pointed to some of the fundamental roles of these receptors and ligands in murine physiology [168][169][170][171][172][173][174][175][176].…”
Section: Vmentioning
confidence: 99%
“…Disruption of the GC-C gene results in resistance to pathogenic bacteria that secrete STa and cause acute secretary diarrhea [170,171]. GC-C null mice display no prominent abnormal phenotypes in a disease-free, highly controlled environment; intestinal digestive fluid secretion is not disrupted, and high carbohydrate, fat, protein, or salt diets do not adversely affect the null mice [170,171].…”
Section: H Gc-c Null Micementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, GC-C regulates water and ion transport in the intestine (5). On the other hand, GC-C-deficient mice are viable, develop normally, and are fertile, but they are resistant to STa-induced diarrhea (6,7). However, considering that all vertebrates contain an intestine-specific membrane GC gene, this GC may serve some important yet undefined physiological roles.…”
mentioning
confidence: 99%